(untitled) (Bangladesh Journal of Urology, 2020)
Advancement in imaging techniques has now made it possible for small renal tumors to be detected incidentally. This has led to the use of minimally invasive techniques for treatment of these cases. A 40 year-old woman was diagnosed to have a small renal mass after routine abdominal ultrasonography for epigastric discomfort. Computed tomography scan was used to characterize the mass, and an elective partial nephrectomy was successfully carried out. The procedure is safe, less morbid, and has good oncological outcome. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.49-52